Pengaruh Kedisiplinan Siswa dan Lingkungan Belajar terhadap Hasil Belajar Kognitif PAK-BP di SMP Katolik Sta. Theresia Tanawangko - Untu, Hadi Ignatius; Wouwo, Febiola Dominica Voice (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2024)
This research aims to find out how student discipline and the learning environment at Sta. Catholic Middle School. Theresia Tanawangko, as well as to determine whether or not there is an influence between student discipline and the learning environment on PAK-BP cognitive learning outcomes at Sta Catholic Middle School. Theresia Tanawangko. The research method used is a quantitative research method which aims to find out whether there is a large influence between the independent variable X1 on the dependent variable Y, whether there is a large influence between the variable large and significant to Y. The sample for this study consisted of 75 respondents obtained by calculating the Slovin formula. Validity and reliability tests were carried out using IBM SPSS 16 for windows and all questionnaire items and tests distributed were declared valid and reliable. The results of this study show that there is a significant influence between student discipline variables on the PAK-BP cognitive learning outcome variables by 31.8%, learning environment variables on PAK-BP cognitive learning outcome variables by 24.3%, and student discipline and environment variables. learning together on the PAK-BP cognitive learning outcome variable was 36% with a significance value of 0.000. This shows that there is an influence of student discipline and the learning environment on PAK-BP cognitive learning outcomes at Sta. Catholic Middle School. Theresia Tanawangko.